PENGEMBANGAN EKOWISATA BAHARI BERBASIS SUMBERDAYA PULAU-PULAU KECIL DI PULAU SAYAFI DAN LIWO, KABUPATEN HALMAHERA TENGAH - Koroy, Kismanto; Yulianda, Fredinan; Butet, Nurlisa A. (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The coastal areas in Sayafi and Liwo islands have the potential of natural resources that are classified as still quite high. The potential of natural resources owned by the two islands reflected on coral reefs, reef fish, ornamental fish, seagrass beds and fisheries. In addition to ecological function, this ecosystem also have a high aesthetic value to the development of marine tourism. The purpose of this study is to determine the suitability index and carrying capacity of the marine ecotourism for the type of diving and snorkeling activities that can be developed on the island Sayafi and Liwo Patani subdistrict of North Central Halmahera in North Maluku province. The results showed that the suitability index of marine ecotourism Sayafi and Liwo islands are in the appropriate category and very appropriate category with the capacity for this type of diving tourism activities 260 people/day in the area of the utilization is equal to 18.07 ha, and for snorkel tour with the utilization is equal to 16.01 ha area, tourists can accommodate as many as 231 people/ day. So, the total tourists who can fit both types of tourist activities is equal to 491 people/day.